Auditor switching: Analisis berdasar pergantian manajemen, financial distress, rentabilitas, dan ukuran kantor akuntan publik - Hestyaningsih Hestyaningsih; Martini Martini; Mega Anggraeni (Penerbit Goodwood, 2020)
Purpose: This study aims to determine the factors that influence auditor switching. Research methodology: The data in the form of financial statements audited by mining companies listed on the Indonesia Stock Exchange (BEI) for the 2013-2017 period totaling 53 companies, a research sample of 5 years. The data analysis technique used is logistic regression analysis. Results: Change of management has a positive and significant effect on auditor switching while financial distress, profitability and size of the Public Accounting Firm have no significant effect on audior switching. Limitations: The limitation of the problem in this study is the dependent variable in the form of auditor switching and the independent variable, namely management change, financial distress, profitability and the size of the public accounting firm; with a sample of research on mining sector companies from 2013-2017. Contribution: For companies, this research is expected to make practical contributions about the information of what factors can influence the company's decision to change auditors. Keywords: Auditor Swicthing, Change of Management, Financial Distress, Profitability, Size of Public Accounting Firm (KAP)